2000
DOI: 10.1073/pnas.040545897
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of a Plasmodium falciparum intercellular adhesion molecule-1 binding domain: A parasite adhesion trait implicated in cerebral malaria

Abstract: Binding of infected erythrocytes to brain venules is a central pathogenic event in the lethal malaria disease complication, cerebral malaria. The only parasite adhesion trait linked to cerebral sequestration is binding to intercellular adhesion molecule-1 (ICAM-1). In this report, we show that Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) binds ICAM-1. We have cloned and expressed PfEMP1 recombinant proteins from the A4tres parasite. Using heterologous expression in mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
195
1
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(205 citation statements)
references
References 32 publications
7
195
1
2
Order By: Relevance
“…Cells were analyzed for surface expression by immunofluorescence 48 hours later with mAb 179 (Affymax Research Institute), which recognizes an epitope tag at the carboxy terminal of the insert. 31,36 Cell lines stably expressing CIDR-1 domains were transfected and selected as described elsewhere. 29,31,36 …”
Section: Mammalian Cell Cultures and Transfectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cells were analyzed for surface expression by immunofluorescence 48 hours later with mAb 179 (Affymax Research Institute), which recognizes an epitope tag at the carboxy terminal of the insert. 31,36 Cell lines stably expressing CIDR-1 domains were transfected and selected as described elsewhere. 29,31,36 …”
Section: Mammalian Cell Cultures and Transfectionmentioning
confidence: 99%
“…31,36 Cell lines stably expressing CIDR-1 domains were transfected and selected as described elsewhere. 29,31,36 …”
Section: Mammalian Cell Cultures and Transfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…DBL-1a, with its clusters of glycosaminoglycan (GAG)-binding motifs, is believed to mediate the formation of rosettes (i.e. binding of infected erythrocytes to uninfected erythrocytes) (Chen et al 1998), which have been linked to the pathogenesis of CM (Newbold et al 1999), whereas DBL-1b binds to ICAM-1 (Smith et al 2000 ;Oleinikov et al 2009) and DBLc binds to chondroitin suphate A (CSA) (Reeder et al 1999 ;Buffet et al 1999 ;Gamain et al 2004), the latter interaction mediating tissue-specific sequestration of pRBC in the placenta. Disease association studies have suggested that differences in CIDRs and DBLs between commonly expressed var genes may contribute to variations in parasite virulence Normark et al 2007), such that some parasite isolates are more likely than others to sequester in particular tissues and therefore cause differing clinical presentations, but -with the exception of particular PfEMP-1 molecules that favour placental sequestration (Fried and Duffy, 2002 ;Salanti et al 2004) -direct evidence to support this hypothesis is lacking.…”
Section: P a R A S I T E L I G A N D S M E D I A T I N G Prbc S E Q Umentioning
confidence: 99%